Intermolecular-force-driven anisotropy breaks the thermoelectric trade-off in n-type conjugated polymers - Rosas Villalva, Diego; Derewjanko, Dennis; Zhang, Yongcao; Liu, Ye; Bates, Andrew; Sharma, Anirudh; Han, Jianhua; Gibert-Roca, Martí; Arteaga, Osnat Zapata; Jang, Soyeong; Moro, Stefania; Costantini, Giovanni; et al. (Nature materials, 2025)
Controlling the molecular orientation of conjugated polymers is a vital yet complex process to modulate their optoelectronic properties along with boosting device performance. Here we propose a molecular-force-driven anisotropy strategy to modulate the molecular orientation of conjugated polymers. This strategy relies on the intermolecular interactions, gauged by the Hansen solubility parameters framework, to provide solvent selection criteria for conjugated polymers that render films with a preferential orientation. We showcase molecular-force-driven anisotropy to overcome the inverse coupling between the electrical conductivity and Seebeck coefficient in solution-processed organic thermoelectrics, a major challenge in the field. Our kinetic Monte Carlo simulations suggest that edge-on orientations break the trade-off by increasing the in-plane delocalization length. The molecular-force-driven anisotropy approach yields a power factor of 115 μW m−1 K−2 and a figure of merit of 0.17 at room temperature for the doped n-type 2DPP-2CNTVT:N-DMBI system. This power factor is 20 times larger than that of conventional doping approaches.
Gesehen am 05.11.2025